Pemberdayaan Teknologi Digital dalam Pemblajaran di SMP NW Mataram melalui Program Kampus Mengajar - Kasyif, Muhammad Kasyiful Kurabi; Azmi, Ema Suryani; Arini Sholeha, Lidya (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The Kampus Mengajar Program aims to improve the quality of education in schools through collaboration between students and teaching staff. This article discusses the implementation of digital technology in learning at NW Mataram junior high school, with the aim of improving students' literacy, numeracy and digital skills. Implementation methods include observation, teaching assistance, technology training, and learning assessment. The results show that the use of digital technology such as interactive PowerPoint, learning applications, and online-based assessments increases student motivation and understanding. However, obstacles such as limited internet access are still a challenge. Recommendations are given to strengthen training for teachers and students in optimal use of digital technology.